Investment Decision Analysis Using the Stochastic Oscillator and Moving Average Convergence Divergence (MACD) Indicators at Indofood Company - Ningsih, Putu Tirta Sari; Gusvarizon, Muhammad; Febriansyah, Febi (Ilmu Ekonomi Manajemen dan Akuntansi, 2025)
This research aims to analyze the stock investment decisions of PT. Indofood Sukses Makmur Tbk (INDF) uses Moving Average Convergence Divergence and stochastic oscillator indicators. The research methodology used is a qualitative method with the type of panel data (time series) obtained from the Indonesia Stock Exchange. The sampling technique uses purposive sampling method with daily data and research periods from 2020. The data analysis technique used is technical analysis using the Moving Average Convergence Dicergence Indicator and Stochastic Oscillator to determine buy & sell signals with the help of the Chart Tradingview program to find out the level of accuracy of both technical indicators on the stock to be invested. The results of this study show that the price movement of PT. Indofood Sukses Makmur Tbk (INDF) using the Moving Average Convergence Divergence (MACD) indicator and Stochastic Oscillator indicator 2020. The results of the study contained a total of 4 (four) Buy signals and 4 (four) Sell signals. With an accuracy rate of 100% during the 2020 period. Meanwhile, the level of risk and return generated using the Moving Average Convergence Divergence and Stochastic Oscillator indicators during the 2020 period on INDF shares obtained a risk of Rp 0 or 0% with a return of Rp 3,550 or 64.79 %.